A STUDY OF RENE DESCARTES' PHILOSOPHY OF RATIONALISM IN THE CONTEXT OF LAW IN INDONESIA - Dendy, Alfi; Mustaufiq, Mustaufiq; Amren, Amren; Ibanes, Reivo; Malau, Parningotan (FOCUS: Jurnal of Law, 2024)
This study examines the influence of René Descartes' rationalist philosophy on the development of Indonesian law, particularly through the framework of Law No. 12 of 2011 on the Formation of Legislative Regulations. Descartes' emphasis on reason as the primary tool for acquiring knowledge and truth is analyzed within the context of legal interpretation in Indonesia. Using a juridical-normative approach, this research reviews secondary data, including legal texts and academic articles, to explore how Descartes' rationalism has shaped the interpretation and application of law in Indonesia. The study concludes that Descartes' principles of logical and systematic reasoning play a crucial role in the formation of legal norms in Indonesia, promoting a legal system that prioritizes clarity, consistency, and justice. The research also highlights the continued relevance of Descartes' ideas in contemporary legal practices and underscores the importance of integrating rationalism into legal philosophy to achieve fair and transparent governance.